Penta Helix Collaboration In Improving Madrasah Achievement - Azhar , Ade Wahyuni; Nasrun, Hasnan; Ramadhani , Aqila Nasya (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study discusses the successful implementation of Pentha Helix Collaboration in improving the achievement of madrasahs at MTs Negeri 2 Deli Serdang in an effort to solve the problems of educational facilities and infrastructure. Involving five main elements—government, business, academics, community, and media—this collaboration was designed in a planned and systematic manner to answer the urgent needs of madrasahs in improving the quality of educational services. This research is included in qualitative descriptive research. Data collection techniques in this study used observation, interviews and documentation. Data analysis used was data collection, data reduction, data presentation, and drawing conclusions/verification.The results of the implementation show that the synergy between the elements of Pentha Helix is ​​able to accelerate the procurement of classrooms, rehabilitation of facilities, and improvement of other supporting infrastructure. Real contributions from each party, such as CSR funding, technical assistance, community involvement, and media publications, have a significant impact on the progress of madrasahs. This success proves that a collaborative approach based on Pentha Helix can be a strategic and sustainable model in the development of education based on multi-party participation.